Dynamic evaluation of simulated leg length inequalities and their effects on the musculoskeletal apparatus - Beeck, Aylin; Quack, Valentin; Rath, Bjorn; Wild, Michael; Michalik, Roman; Schenker, Hanno; Betsch, Marcel (Gait & Posture, 2019)
Background: Leg length inequalities (LLI) are a common problem in medicine. So far, the diagnosis and treatment are performed under static conditions. Surface Topography (ST) is an optical, non-invasive technique that uses the principle of triangulation to measure spinal posture and pelvic position. This technique offers the opportunity to detect and treat LLIs and their effects under dynamic conditions. Research: question The aim of the study is to show that ST can detect simulated LLIs under dynamic conditions and to prove if there are differences between the effects on the human body under static and dynamic conditions. Methods: In the clinical study a total of 30 test subjects were examined with a ST measuring device. LLIs (1 to 4 cm) were simulated using a custom- built sandal and insoles of various thickness. The pelvic obliquity, the surface rotation and lateral deviation of the spine were detected on a treadmill under static and dynamic conditions (3 km/h). Results: Under static and dynamic conditions LLIs lead to a significant increase of all measured parameters. The pelvic obliquity reaches a significant level of p < 0.0001 under static and p = 0.0001–0.0421 under dynamic conditions. However, for all examined parameters the magnitudes of the parameters under dynamic conditions were smaller than under static conditions. Significance: The study showed that simulated LLIs also have a significant effect on the human pelvis and spine under dynamic conditions, but with a smaller magnitude than under static conditions. The human individuum is a dynamic one. Because of that, for the future it should be of great interest to use dynamic measurements to detect and treat LLIs to provide an over correction of LLIs.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Dynamic; Gait; Leg length discrepancy; Leg length inequality; Rastereography; Static; Surface topography